Hubungan Pemberian Susu Formula dengan Kejadian ISPA pada Bayi Usia 6-12 Bulan di Desa Tarai Bangun Wilayah Kerja Puskesmas Tambang Tahun 2022: Formula Milk, ISPA, Babies Aged 6-12 Months - Nur Elza Syafira,; Apriyanti, Fitri; Afiah, Afiah (Evidence Midwifery Journal, 2025)
Infants who are given formula milk after 6 months are at lower risk of developing ISPA than infants who are given formula milk before the age of 6 months. This is because infants who are given formula milk from the start have weaker immunity than infants who are given breast milk because infants who are not given breast milk do not get complete nutrition so that infants are more susceptible to disease. The purpose of this study was to determine the relationship between giving formula milk and the incidence of ISPA in infants aged 6-12 months in Tarai Bangun village, Tambang Health Center working area in 2022. The population of this study was all mothers who had infants aged 6-12 months totaling 45 infants with a case sampling technique using total sampling. The measuring instrument used was a questionnaire. The analysis used was univariate and bivariate with the chi square test. Based on the results of the study, out of 45 mothers who had infants aged 6-12 months, most of them gave formula milk to their children, as many as 31 people (68.9%) and there was no ISPA as many as 26 people (57.8%). The statistical test results showed a p value = 0.002 (≤ 0.05), which means that there is a relationship between giving formula milk and the incidence of ISPA in infants aged 6-12 months in Tarai Bangun village, Tambang Health Center work area in 2022. It is hoped that the results of this study can be used as input for respondents to provide exclusive breastfeeding to infants aged 0-6 months without being influenced by the promotion of existing formula milk